Disinfection of football protective equipment using chlorine dioxide produced by the ICA TriNova system - DuBois John D; Newsome Anthony L; Tenney Joel D (BMC, 2009)
Abstract Backround Community-associated methicillin-resistant Staphylococcus aureus outbreaks have occurred in individuals engaged in athletic activities such as wrestling and football. Potential disease reduction interventions include the reduction or elimination of bacteria on common use items such as equipment. Chlorine dioxide has a long history of use as a disinfectant. The purpose of this investigation was to evaluate the ability of novel portable chlorine dioxide generation devices to eliminate bacteria contamination of helmets and pads used by individuals engaged in football. Methods In field studies, the number of bacteria associated with heavily used football helmets and shoulder pads was determined before and after overnight treatment with chlorine dioxide gas. Bacteria were recovered using cotton swabs and plated onto trypticase soy agar plates. In laboratory studies, Staphylococcus aureus was applied directly to pads. The penetration of bacteria into the pads was determined by inoculating agar plates with portions of the pads taken from the different layers of padding. The ability to eliminate bacteria on the pad surface and underlying foam layers after treatment with chlorine dioxide was also determined. Results Rates of recovery of bacteria after treatment clearly demonstrated that chlorine dioxide significantly (p < 0.001) reduce and eliminated bacteria found on the surface of pads. For example, the soft surface of shoulder pads from a university averaged 2.7 × 103 recoverable bacteria colonies before chlorine dioxide treatment and 1.3 × 102 recoverable colonies after treatment. In addition, the gas was capable of penetrating the mesh surface layer and killing bacteria in the underlying foam pad layers. Here, 7 × 103 to 4.5 × 103 laboratory applied S. aureus colonies were recovered from underlying layers before treatment and 0 colonies were present after treatment. Both naturally occurring bacteria and S. aureus were susceptible to the treatment process. Conclusion Results of this study have shown that chlorine dioxide can easily and safely be used to eliminate bacteria contamination of protective pads used by football players. This could serve to reduce exposure to potential pathogens such as the methicillin-resistant Staphylococcus aureus among this group of individuals.